2021
DOI: 10.3390/en14206675
|View full text |Cite
|
Sign up to set email alerts
|

Mining-Induced Seismicity during Development Works in Coalbeds in the Context of Forecasts of Geomechanical Conditions

Abstract: Mining-induced seismicity in the area of development works and proper mining operations is one of the major determinants of the rockburst hazard level in underground mines. Rockburst hazard assessment in Polish collieries is performed by a variety of mining and geophysical methods, including seismic and seismoacoustic techniques, borehole surveys, small diameter drilling, rock strata profiling and analyses of geomechanical properties of rocks, geological structure and geological mining conditions. In the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is the great signifcance to study the mechanism of coal, rock, and gas compound dynamic disaster and its previous identifcation. Te typical studies on the efect of mining engineering and mechanism of coal mine earthquake and rock burst also include references [30][31][32][33][34][35][36]. Tese studies mainly used the numerical simulation, theoretical analysis, feld tests, and laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It is the great signifcance to study the mechanism of coal, rock, and gas compound dynamic disaster and its previous identifcation. Te typical studies on the efect of mining engineering and mechanism of coal mine earthquake and rock burst also include references [30][31][32][33][34][35][36]. Tese studies mainly used the numerical simulation, theoretical analysis, feld tests, and laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of coal mining, these thick and hard rock strata are not easy to break. However, as the mining space increases, the overhanging roof area of the hard-thick strata keeps increasing and begins to accumulate a large amount of elastic energy, and when the breaking limit is reached, the hardthick strata will break and release the accumulated energy [1][2][3] , thus inducing many strong dynamic disaster phenomena such as strong mine earthquake, mine water burst, and roof falling [4][5][6][7][8] . Take Ordos area in China as an example, there are thick and hard rock strata mainly medium and fine grained sandstone in the Cretaceous strata, which have high strength, large thickness and distance from coal seams.…”
Section: Introductionmentioning
confidence: 99%
“…Baranov et al (2021) studied the characteristics of the spatial distribution of mining-induced seismicity events induced by geotectonic activation under mining conditions and developed a model of the maximum distance from the source of mining-induced seismicity to the predicted induced aftershock. Chlebowski et al (2021) investigated the qualitative and quantitative indicators characterizing the seismic activity of rock formations, established a stress state analysis model to predict mining-induced seismicity levels, and verified the correlation between changes in mining-induced seismicity activity and model tests. Sokoła-Szewioła et al (2019) studied the use of a GIS classification system to predict and evaluate the effects of mining-induced seismicity on surface buildings, the results of which showed that numerous information on mining-induced seismicity-induced ground vibrations, including object damage, can be recorded using the ArcGIS system.…”
Section: Introductionmentioning
confidence: 99%